Biopreservative activities of Lactobacillus plantarum strains in fermenting cassava fufu - Obadina, A.O.; Oyewole, O.; Sanni, Lateef O.; Tomlins, Keith I. (2006)
The growth of three pathogens, namely Escherichia coli, Staphylococcus aureus and Salmonella typhii were investigated in fermenting and non-fermenting cassava. The pH of the steeped cassava was also examined during fermentation. Antimicrobial effects of the Lactobacillus plantarum on the pathogens were also determined by agar diffusion method. All the pathogens were inhibited by L. plantarum strains with Staph. aureus having the highest inhibitory zone followed by E. coli and S. thyphii. However, in the fermenting cassava, the pathogens increased in population within the first 36 h of the process and decreased to complete extinction after the 96 h of fermentation. The L. plantarum exhibited high but varying degree of inhibition on the pathogens. The findings justify the bio-preservative roles of lactic acid bacteria in traditional cassava products.